Feasibility of Monte Carlo modelling for the neutron-neutron logging tool response in specific geological models - Wiącek, Urszula; Woźnicka, Urszula (Geology, Geophysics and Environment, 2017)
Neutron well logging is one of the basic methods for the determination of the characteristic parameters of rock samples. The neutron source and neutron detectors are elements of Neutron-Neutron Thermal-Epithermal logging tool (NNTE) of significant importance. A neutron source creates the neutron field in the nearest environment. Detectors placed at specified distances from the source register neutrons from this space. A signal of a Neutron-Neutron Thermal-Epithermal tool in specific geological conditions was numerically calculated by means of the Monte Carlo (MC) codes. The main aim of this paper is to show the potential for using the Monte Carlo N-Particle Transport Code (MCNP) software in nuclear well logging prospection methods. The results of this MC modelling are presented in this paper.